Análisis de la calidad del servicio que presta el hotel Santonni de la ciudad de Loja, provincia de Loja - Ecuador - Songor Cango, Bryan Andrés (2023)
The purpose of this study was to analyze the quality of services provided by the Santonni Hotel in Loja. In order to determine the quality of service provided by the hotel, a diagnosis was made of the current situation. In addition, it was proposed improvement strategies to increase the quality of hotel services. The methodology used was descriptive and cross-sectional. Diagnose and SWOT analysis were conducted through direct observation, while questionnaire-type instruments were employed for surveys and interviews. The survey was validated using SPSS version 25. A total of three staff members were interviewed and 360 surveys administered to hotel clients. The results showed that the hotel had all the operating permits and standards of a three-star hotel. Employees have a positive working environment, and economic incentives match their needs and expectations. However, employees do not receive training, the hotel does not have a service rating system, and it does not have a quality management system. Additionally, guests stated their perception exceeded their expectations. In all dimensions the highest ratings are in the categories "very satisfied" and "satisfied", followed by a lower percentage of "neither satisfied nor dissatisfied" and only 0.28% rated "dissatisfied" on certain items. Based on the lowest values, strategies were formulated and designed to provide better service.